Structural Electromagnetic Absorber Based on MoS2/PyC-Al2O3 Ceramic Metamaterials - Liu, Xingmin; Liu, Heqiang; Wu, Hongjing; Zhou, Qian; Liang, Hongsheng; Liu, Guoqiang; Duan, Wenyan; Gu, Yue; Xu, Chengying; Travitzky, Nahum; Colombo, Paolo; Riedel, Ralf (Small, 2023)
Limited by the types of suitable absorbents as well as the challenges in engineering the nanostructures (e.g., defects, dipoles, and hetero-interface) using state-of-the-art additive manufacturing (AM) techniques, the electromagnetic (EM) wave absorption performance of the current ceramic-based materials is still not satisfying. Moreover, because of the high residual porosity and the possible formation of cracks during sintering or pyrolysis, AM-formed ceramic components may in many cases exhibit low mechanical strength. In this work, semiconductive MoS2 and conductive PyC modified Al2O3 (MoS2/PyC-Al2O3) ceramic-based structural EM metamaterials are developed by innovatively harnessing AM, precursor infiltration and pyrolysis (PIP), and hydrothermal methods. Three different meta-structures are successfully created, and the ceramic-based nanocomposite benefit from its optimization of EM parameters. Ultra-broad effective absorption bandwidth (EAB) of 35 GHz is achieved by establishment of multi-loss mechanism via nanostructure engineering and fabrication of meta-structures via AM. Due to the strengthening by the PyC phase, the bending strength of the resulting ceramics can reach ≈327 MPa, which is the highest value measured on 3D-printed ceramics of this type that has been reported so far. For the first time, the positive effect deriving from the engineering of the microscopic nano/microstructure and of the macroscopic meta-structure of the absorber on the permittivity and EM absorption performance is proposed. Integration of outstanding mechanical strength and ultra-broad EAB is innovatively realized through a multi-scale design route. This work provides new insights for the design of advanced ceramic-based metamaterials with outstanding performance under extreme environment.
CRIS-Team Scopus Importer:2023-05-05
Keywords: additive manufacturing; mechanical strength; metamaterials; MoS; multi-loss mechanism